The Relationship Between Critique of History and Metahistory:A Proposal - Abolhasan Fayaz Anush (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It is said that the relationship between history and theory is like “the deaf dialog”. It means that there are incongruous interests between them, and maybe the interpretation itself, causes an inconsistent relation between historians and theorists. The present paper explains that every historian needs to have a theoretical base for writing and studying history. Then, it emphasizes that to criticize the historical works the critics must be aware of the theoretical base they criticize, and they themselves have to adopt a specific theoretical base. So, every theoretical base is pertinent to the metahistorical field, and it means that the historians who theorize have to attend to necessaries more than facts gathering. Therefore, the most necessary debate is an explanation of the relationship between the critique of history and metahistory. The paper analyzes different levels of historical knowledge to explain the relationship.